2002
DOI: 10.1128/mmbr.66.4.630-670.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role ofRAD52Epistasis Group Genes in Homologous Recombination and Double-Strand Break Repair

Abstract: The process of homologous recombination is a major DNA repair pathway that operates on DNA double-strand breaks, and possibly other kinds of DNA lesions, to promote error-free repair. Central to the process of homologous recombination are the RAD52 group genes (RAD50, RAD51, RAD52, RAD54, RDH54/TID1, RAD55, RAD57, RAD59, MRE11, and XRS2), most of which were identified by their requirement for the repair of ionizing-radiation-induced DNA damage in Saccharomyces cerevisiae. The Rad52 group proteins are highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
1,028
1
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 926 publications
(1,065 citation statements)
references
References 457 publications
(646 reference statements)
28
1,028
1
8
Order By: Relevance
“…The lagging strand could provide a template for elongation of the terminated leading strand. Reinstalling of the replication fork via HR could proceed by invasion of the terminated strand into the sister chromatid duplex and elongation of the 3 end, followed by disruption of the D-loop in a mechanism similar to synthesis-dependent strand annealing (SDSA; Symington, 2002). Another type of DNA damage arising during DNA synthesis and manageable by HR are double-stranded ends.…”
Section: Introductionmentioning
confidence: 99%
“…The lagging strand could provide a template for elongation of the terminated leading strand. Reinstalling of the replication fork via HR could proceed by invasion of the terminated strand into the sister chromatid duplex and elongation of the 3 end, followed by disruption of the D-loop in a mechanism similar to synthesis-dependent strand annealing (SDSA; Symington, 2002). Another type of DNA damage arising during DNA synthesis and manageable by HR are double-stranded ends.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have found an involvement of Rad54 protein in homologous recombination and the DNA homology-directed elimination of DNA breaks and other chromosome lesions [3,17]. Consistent with the genetic data, studies with purified proteins have shown synergistic interactions of Rad54 with Rad51, in a manner that (1) greatly improves the ability of Rad51 to mediate the DNA strand invasion reaction with both naked and chromatinized DNA templates, and (2) enhances the ATPase, DNA supercoiling, DNA strand opening, DNA branch migration, and chromatin remodeling functions of Rad54 [9,10,[12][13][14]16].…”
Section: Discussionmentioning
confidence: 99%
“…Like many members of the Swi2/Snf2 protein family, Rad54 remodels chromatin structure, and this chromatin remodeling activity requires ATP hydrolysis [12][13][14]. Moreover, Rad54 utilizes the free energy from ATP hydrolysis to accelerate the DNA strand transfer reaction [15,16] and to process branched DNA structures [16], including the Holliday junction [16], that are expected to be generated during certain HR reactions [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations